ANALISIS FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI PERIODE 2019-2023 - Septiani, Andini; Nurmansyah, Agung; Saraswati, Esti (Politeknik Bisnis Indonesia, 2024)
The purpose of this study is to determine and investigate how tax planning, tax avoidance, deferred tax expense, business strategy, and leverage affect the management of earnings in insurance firms that are listed on the BEI between 2019 and 2023. Purposive sampling was used to choose the research sample, yielding 17 sample companies. Secondary data, which was gathered from www.idx.co.id and the businesses' official websites, is the sort of data that was used. Multiple regression analysis is the analysis technique used, and SPSS software is used for this purpose. The findings demonstrate that deferred tax expense variables and tax planning have a favorable and noteworthy impact on earnings management. On the other hand, company strategy, tax evasion, and leverage factors have a negative and substantial impact on earnings management.